EVALUATE THE QUALITY OF SERVICES PROVIDED IN UNIVERSITIES USING THE ACTUAL PERFORMANCE MODEL / SERVPERF /APPLIED RESEARCH AT AL-ESRAA UNIVERSITY (American Journal of Business Management, Economics and Banking, 2024)
The research aims to use the SERVPERF model to achieve service quality at Esraa University College, by standing on the theoretical basis for assessing service quality according to the SERVPERF performance model, as well as identifying the level of university service quality, and the importance of research with an active contribution to service quality is to increase the need to develop colleges due to the economic, social and cultural changes that society is witnessing. The descriptive aspect was relied upon by adopting the questionnaire form as a main tool for collecting data because it fits a lot of descriptive and exploratory research and studies, and the research used the statistical program (SpssVar.23) in addition to applying a set of appropriate statistical methods. The research was based on the SERVPERF model, which is a multi-component scale developed to assess customer perceptions about the quality of service in the service sector. The research concluded with a set of conclusions as: The majority of the members of the research sample evaluate the quality of the service provided to them through the appropriateness of the external appearance and the facilitation of the internal appearance, and they show a consensus on their feeling of confidence and the ability of the individuals in the college the sample of the research to show respect for them. And a set of recommendations that are consistent with these conclusions as: The continuation of the college with an emphasis on commitment, development and continuous improvement of the educational plan in the college the research sample.